Konflik Hukum Perkawinan Beda Agama di Indonesia (Studi Penetapan Hakim Nomor: 12/Pdt.P/2022/Pn Ptk) - Adella Yuana; Ilka Sandela (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Article 1 of Law Number 1 of 1974 concerning Marriage (hereinafter referred to as the Marriage Law) which states "Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. Almighty". Creating physical and spiritual bonds in forming a marriage must meet the terms and conditions. Fulfillment of these terms and conditions aims to ensure that a marriage is considered valid both religiously and stately. Article 2 paragraph (1) of the Marriage Law states that "Marriage is legal, if it is carried out according to the laws of each religion and belief". In particular, Article 40 letter c of the Compilation of Islamic Law prohibits interfaith marriages in Islam. In the case with the Judge's Determination Number: 12/Pdt.P/2022/PN Ptk, the request was granted by the judge to be recorded at the Population and Civil Registry Office. This incident created legal conflicts and uncertainty over the norms of interfaith marriages. The purpose of this study is to identify and analyze legal conflicts and legal certainty of interfaith marriages in Indonesia through case studies. The research method used in this research is normative juridical. The result of this research is invalid based on Article 40 letter c of the Compilation of Islamic Law. Indonesian Positive Law regulates a legal marriage if it is in accordance with Article 2 paragraph (1) of the Marriage Law. Based on religion and belief, Islam clearly prohibits interfaith marriages. The judge in this case handed down the determination based on the norms of Article 35 of Law Number 23 of 2006 concerning Population Administration which opens the opportunity for interfaith marriages to be recorded at the Population and Civil Registry Office. The occurrence of conflicting norms for interfaith marriages in Indonesia results in the uncertainty of marriage law in its regulations.